Hubristic leadership: A review. (November 2017) - Sadler-Smith, Eugene; Akstinaite, Vita; Robinson, Graham; Wray, Tim
Hubristic leaders over-estimate significantly their own abilities and believe their performance to be superior to that of others; as a consequence, they make over-confident and over-ambitious judgements and decisions. The fact that hubristic leaders tend to be resistant to criticism, and invulnerable to and contemptuous of the advice of others further compounds the problem. In this article, we review conceptual, theoretical and methodological aspects of hubristic leadership research. We examine hubristic leadership from two standpoints: first, from a psychological and behavioural perspective, we review hubris in terms of over-confidence and its relationship to core self-evaluation and narcissism; second, from a psychiatric perspective, we review hubris as an acquired disorder with a distinctive set of symptoms (Hubris Syndrome), the onset of which is associated with the acquisition of significant power. In doing so, we draw distinctions between hubris and several related constructs, such as over-confidence, narcissism, core self-evaluation and pride. Methodologically, we review how hubris and Hubris Syndrome can be recognised, diagnosed and researched, and we explore some of the unique challenges and opportunities hubris research presents. We conclude by offering some directions for future inquiry and recapitulate the practical and pedagogical significance of this vitally important but under-researched leadership phenomenon.